(untitled) (Journal of Information Technologies in Education (ITE), 2015)
The article analyzes the problem of readiness of students of different specialties to use information technology in the educational process of higher education. Particular attention is paid to contemporary processes of globalization and informatization of higher education as a priority trends of modern Ukrainian society. Experimental data provided in the publication are comparative characteristics of the students using different specialty areas and preparation of information technologies in education. Computerization of the educational process - one of the main priorities in the development of higher education, a new stage for the entire higher education system, promising improvements in the direction of learning in higher education.